Job share a consultant post. Issue 6866 (5th December 1992) - Thornicroft, G.; Strathdee, G.
Abstract : Job sharing offers advantages to both employer and employee but it is still uncommon in medicine. Based on the experiences of two psychiatrists sharing a consultant post this article describes some of the problems in obtaining a job share. The most difficult part can be getting an interview, and once a post has been obtained the terms and conditions of service may have to be modified to suit job sharing. Getting on well with your job sharing partner and good communication will not only help overcome the obstacles but ensure that the sharing is successful.